PENGARUH BETA SAHAM TERHADAP EXPECTED RETURN DENGAN MODEL CAPITAL ASSET PRICING PADA PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA - Etty M. Nasser (Media Riset Akuntansi, Auditing & Informasi, 2007)
The objective of this research is to obtain empirical evidence of whether market beta has a significant influence on the expected return. This research examines 30 manufacturing companies listed in Jakarta Stock Exchange during 2001-2005 period. Data are mostly secondary data, obtained from Indonesian Capita! Market Directory and annual reports of the companies from 'Pusat Referensi Pasar Modal Indonesia' in Jakarta Stock Exchange. The statistical method used to test the hypothesis is multiple regression. The test of heteroskedasticity, multicolinearity and autocorrelation used in this research are entirely suitable and unbiased.The empirical result of this research indicates that market beta has a significant influence on the expected return, either individual equity or portfolio equity. This result supports the CAPM theory which shows a positive correlation between risk and expected return. However, this result contradicts the research's result of both Eugene F. Fama and Kenneth R. French which shows a negative correlation between risk and expected return. The result would be different if other independent variables such as size, earning price ratio (E/P), book leverage (A/BE), market leverage (A/ME), book to market equity (BE/ME) were being tested together. Beta market and BE/ME were the two variables that have a significant influence on the expected return.Keywords: beta market, beta portfolio, risk, expected return, CAPM, size, earning price ratio, book leverage, market leverage, book to market equity